Pengaruh Benzil Aminopurin (BAP) terhadap Induksi Tunas dari Nodus anggrek Dendrobium mussauense - Media Media; Zozy Aneloi Noli (Universitas Andalas, 2024)
Dendrobium mussauense has attractive flowers and potential as a parent of a hybrid orchid. The color of this species is cream with violaceous purple venations on the labellum. D. mussauense is an orchid species listed as vulnerable in IUCN. This species is not located in protected areas nor known to be conserved ex-situ. Clonal propagation is an important biotechnological tool for the conservation of orchids. Thin cell layer (TCL) is a micropropagation method using thin-sized explants that facilitate the diffusion of nutrients to tissues. This study examined induction shoot through two explant cutting techniques, namely TCL and non-TCL explant, at various concentrations of BAP. The non-TCL explant was more effective than the TCL explant in inducing the shoot of D. mussauense. The half-strength Murashige and Skoog (MS) medium supplemented with 0.9 mg.L-1 BAP was a suitable concentration to induce the shoot of D. mussauense through non-TCL explant. The average shoot length was 1,8 cm, and the average number of shoots was 5/explant.